2020
DOI: 10.3390/ma13040900
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion-Fatigue Failure of Gas-Turbine Blades in an Oil and Gas Production Plant

Abstract: This paper investigates the root cause of a failure in gas-turbine blades, made of Nimonic-105 nickel-based superalloy. The failure was reported in two blades in the second stage of a turbine-compressor of a gas turbine in the hot section. Two failed blades were broken from the root and from the airfoil. The failure took place after 20 k h of service exposure in the temperature range 700–850 °C, with the rotating speed being in the range 15,000–16,000 rpm. The microstructures of the failed blades were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Stolarz and Foct [31] have investigated the onset of fatigue cracks and their further development. Experimental studies [32][33][34][35][36] have also shown that the microstructure of steel plays a key role in the formation of surface cracking under fatigue loading.…”
Section: Results Of Fatigue Testsmentioning
confidence: 99%
“…Stolarz and Foct [31] have investigated the onset of fatigue cracks and their further development. Experimental studies [32][33][34][35][36] have also shown that the microstructure of steel plays a key role in the formation of surface cracking under fatigue loading.…”
Section: Results Of Fatigue Testsmentioning
confidence: 99%
“…Furthermore, when the implant is used to replace the lost tissue, it will undergo a complicated process, especially for the degradation mechanism. This degradation mechanism is one of the most common reasons for failure [7]. It can be caused by a degradation mechanism that causes a material's volume to decrease [8] that affects the material's toughness.…”
Section: Introductionmentioning
confidence: 99%
“…In corrosive environments, intensive corrosion control methods, such as inhibitors, cathodic protection, and coating, are required to maintain the integrity of the pipes, insufficiency or inadequate measures can even result in the need for early replacement [18]. A more corrosionresistant pipe technology, such as Corrosion-resistant alloys (CRA) and polymer composites, should be chosen to reduce pipeline corrosion.…”
Section: Introductionmentioning
confidence: 99%